Pengembangan Ketrampilan dengan Pelatihan Memasak Aneka Hidangan Ikan Guramekepada Kelompok Ekstra Kurikuler Tata Boga Siswa SMA Permai Pluit Jakarta - Nonot Yuliantoro (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2020)
Skill Development with Cooking Training for Guramek Fish Dishes to the Extra-Curricular Group of Food Catering Students at Permai Pluit High School Jakarta. Cooking is an art to process raw materials into a ready eat the dish with proper cooking methods. To be able to cook well and properly, people need training the right way. Pelita Harapan School of Hospitality and Tourism carry out community service cooking training activities aimed at the cooking club at Permai Senior High School Pluit Jakarta. The purpose of this community service is to share cooking skill and knowledge with the member of the cooking club at Permai High School Pluit Jakarta since they need assistance to improve their cooking and food presentation skill. A pre-test was conducted before the training to find out the basic skill and knowledge of cooking especially gurame fish; the ending of community service activities was carried out in the post-test to determine the effectiveness of the gurame cooking training that had done. Cooking training activities to the member of the cooking class Permai High School Students has a positive influence because the cooking club member became more skillfully and understand in processing gurame into various Nusantara Recipes.